PEMBELAJARAN MENULIS ESAI DENGAN PENDEKATAN KONTEKSTUAL DAN MEDIA VIDEO DI KELAS XI SMA DARUL ‘ULUM SUGIO - Ummu Rosyidatul; Mustofa Mustofa; Nisaul Barokati Selirowangi (LPPM UNISDA, 2019)
This research aims to download have been described : (1) the activity of the students on learning to write essays with a contextual approach and video media, (2) the activity of the teacher in the learning of essay writing with the contextual approach and video media, (3) student learning completeness on learning to write a contextual approach to essay and video media, and (4) student response on learning to write essays with the contextual approach and media video in class XI SMA Darul Ulum Sugio. This type of research is research qualitative and quantitative test results through the application of approaches and learning media. The population of this research is the learners class XI SCIENCES 2 SMA Darul Ulum Sugio. This research data obtained through observation sheets students, teacher observation sheets, test write essays, and question form. The results showed that the application of the approach Contextual Teaching and Learning (CTL) and video media on learning writing essay very effectively applied. Ditinjau of the student activity categorized either by percentage of 87% or effective to apply, review of teacher's activity categorized either by percentage amounted to 93.75% or effective to apply, review of ketuntasan learning students categorized either by a percentage of 75% effective or to be applied, in terms of response students categorized very well with the percentage of 91.96% or effective to apply.